2017
DOI: 10.1111/resp.13118
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry reference values for population aged 7–80 years in China

Abstract: Background and objective: Lung function tests are widely used in clinical and public health practice; however, no valid spirometry reference values were available for the general population in China. This study aimed to provide valid spirometry predictive equations for the general population in China, and to evaluate the predictive performance of previously used equations. Methods: Data from the China National Health Survey 2012-2015 and the 'Generalized Additive Models for Location, Scale and Shape' statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
1
27
2
Order By: Relevance
“…To the best of the authors’ knowledge, only few studies [1422, 24] aimed at evaluating the applicability of the GLI-2012 norms in healthy adults’ populations. Table 4 presents the main characteristics and results of some studies reporting Z-scores data [1420] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of the authors’ knowledge, only few studies [1422, 24] aimed at evaluating the applicability of the GLI-2012 norms in healthy adults’ populations. Table 4 presents the main characteristics and results of some studies reporting Z-scores data [1420] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the GLI-2012 norms seem unsuitable for clinical use in the Swedish [14] , Finnish [19] and Brazilian [22] populations. Moreover, a Chinese study [24] , concluded that GLI-2012 norms [10] showed unfavorable generalizability to their sample population. An African study [23] has demonstrated that Tanzanians aged 13–29 years, compared to the predicted values for Black populations inhabiting the GLI-2012 norms, scored relatively lower in some spirometric data with the exception of the FEV 1 /FVC (1 st s forced expiratory volume/forced vital capacity) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] and Zhang et al. [ 34 ] as follows: 0, no symptoms, normal stools; 1, repetitive mouth/ear scratching and ear canal digging with hind legs, a few wet and unformed stools; 2, decreased activity, self‐isolation, and puffiness around eyes and/or mouth, wet and unformed stools with some yellow mucus; 3, periods of motionlessness for more than 1 min, lying prone on stomach, and decreased activity, more wet and unformed stools with a lot of yellow mucus; 4, no response to whisker stimuli and reduced or no response to prodding, a larger number of wet and unformed stools with moderate perianal staining of the coat; 5, tremor, convulsion, and death, severe watery stool with severe perianal staining of the coat.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found these reference equations to be unsuitable for some Caucasian and non‐Caucasian populations . For this reason, appropriateness of the GLI‐2012 equations should be confirmed prior to their use for ethnic groups not currently covered by the equations.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several studies have found these reference equations to be unsuitable for some Caucasian and non-Caucasian populations. [15][16][17][18][19][20] For this reason, appropriateness of the GLI-2012 equations should be confirmed prior to their use for ethnic groups not currently covered by the equations. This includes Indigenous Australians who identify as Aboriginal, Torres Strait Islander or both Aboriginal and Torres Strait Islander ('both').…”
Section: Introductionmentioning
confidence: 99%